2018
DOI: 10.1016/j.poly.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Novel derivatives of the antibiotic NHC–Ag(I) drug candidate SBC3: Synthesis, biological evaluation and 109Ag NMR studies

Abstract: The synthesis of six novel N-heterocyclic carbene silver(I) acetate complexes, three symmetrical and three non-symmetrical, were achieved using 4,5-diphenylimidazole to produce intermediate imidazolium salts and then obtain the corresponding silver(I) complexes through complexation with silver acetate via the Youngs' method. In vitro biological testing, using the Kirby-Bauer disk diffusion method, was conducted against Methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli, with a NHC-silver(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…49 In a recent study, it was reported that the carbon atom chemical shifts for benzimidazole complexes were reported in the range of 142.6-149.5 ppm. 48 As expected, the unsaturated ring 13 C shifts (atom nos. 1-6 and13) for compounds 1 and 2 occurred in the ranges of 116.1-137.4 and 116.1-137.5 ppm, whereas they were simulated in the ranges of 118.1-140.4 and 118.4-142.5 ppm in CHCl 3 .…”
Section: Nmr Spectral Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…49 In a recent study, it was reported that the carbon atom chemical shifts for benzimidazole complexes were reported in the range of 142.6-149.5 ppm. 48 As expected, the unsaturated ring 13 C shifts (atom nos. 1-6 and13) for compounds 1 and 2 occurred in the ranges of 116.1-137.4 and 116.1-137.5 ppm, whereas they were simulated in the ranges of 118.1-140.4 and 118.4-142.5 ppm in CHCl 3 .…”
Section: Nmr Spectral Analysissupporting
confidence: 77%
“…As reported in the literature, [42][43][44] this peak was not observed for the Agcarbene because of the fluxional behavior of the NHC complexes. [45][46][47] Furthermore, the chemical shifts of the acidic NCHN proton of the benzimidazolium ligand derivative has been reported at 11.04 48 and 11.25 ppm. 49 In a recent study, it was reported that the carbon atom chemical shifts for benzimidazole complexes were reported in the range of 142.6-149.5 ppm.…”
Section: Nmr Spectral Analysismentioning
confidence: 97%
“…In the refinement of 4, the C11cyclohexyl ring was disordered over two positions. Anisotropic refinement but, with the displacement ellipsoids constrained to be nearly isotropic, led to a site occupancy factor = 0.571 (11) for the major component. The maximum and minimum residual electron density peaks of 1.15 and 1.32 eÅ −3 , respectively, were located 0.98 and 0.75 Å from the H26c and Ag1 atoms, respectively.…”
Section: Single Crystal X-ray Structure Determinationsmentioning
confidence: 99%
“…myocrisin and auranofin, are used for the treatment of rheumatoid arthritis [5]. Notably, silver and its compounds [6,7] and silver-based nanoparticles [8] have long been known to possess strong inhibitory and bactericidal effects as well as a broad spectrum of anti-microbial activities for bacteria, fungi and viruses, and continue to attract significant attention [9][10][11][12]. Silver generally exhibits higher toxicity to microorganisms with lower toxicity to mammalian cells compared with other metals [13].…”
Section: Introductionmentioning
confidence: 99%
“…These salts 91 were stirred with silver acetate in dichloromethane for 3 days to get desired complexes 92 in moderate yield in the range of 12–55 % (Scheme 21). [59] …”
Section: Synthetic Strategiesmentioning
confidence: 99%